Human Displacement, Livelihood Sources and Intensity of Severe Hunger in Somalia During COVID-19: A Zero-Inflated Random Effects Poisson Model - Oyekale, Abayomi (HABITAT, 2025)
Human displacement is a growing problem in Africa. In Somalia, the traumas of human displacement were compounded by the COVID-19 pandemic and other welfare shocks.  These resulted into growing poverty and food insecurity. This study analysed the determinants of severe hunger among Somali households during the COVID-19 pandemic, focusing on displacement status, livelihood sources and other demographic variables. The data were collected in two panels by the Somalia National Bureau of Statistics in 2021-2022, using the stratified random sampling. Data were analysed with Zero-Inflated Random Effects Poisson (ZIP) model within the framework of the Generalized Structural Equation Model (GSEM) in STATA 17. The results showed that the proportion of households not experiencing severe hunger declined from 34.51% to 26.54% in 2021 and 2022, respectively. Exposure to shocks increased markedly, while economic activity and income improvements contracted. The econometric results showed that education, remittances, pensions, NGO assistance, and wage employment reduced hunger severity, whereas sickness, disability, displacement, and exposure to shocks intensified it. Income changes during the COVID-19 pandemic also played a central role, with stagnant or declining incomes strongly associated with higher hunger severity. These findings highlight the multidimensional nature of food insecurity in fragile states with emphases on prioritization of education, wage employment, and shock-responsive safety nets, while scaling up pensions and targeted humanitarian assistance.